Development of a rapid quantitative method to differentiate MS1 vaccine strain from wild-type Mycoplasma synoviae - Liao, Changtao; Chen, Yiquan; Yan, Zhuanqiang; Song, Yiwei; Zhou, Qi; Zhu, Puduo; He, Xudong; Li, Wenyang; Chen, Feng (Frontiers in Veterinary Science, 2024)
Mycoplasma synoviae (MS) is an economically significant pathogen in the poultry industry.Vaccination is an effective method to prevent and control MS infection. Currently two commercially MS live attenuated vaccines are available, one is the temperature sensitive MS-H vaccine strain and the other is NAD-independent MS1 vaccine strain. Differentiation of vaccine strains from wild-type (WT) strains is crucial to monitor MS infection especially after vaccination. In this study, we developed a Taqman duplex real-time polymerase chain reaction (PCR) method to identify MS1 vaccine strain from WT strains. The method was specific, no cross-reaction with other avian pathogens. The sensitivity assay suggested that no inhibition occurred neither between probes nor mixed and pure templates in duplex real-time PCR. Compared with melt-based mismatch amplification mutation assay (MAMA), our method was more sensitive and rapid. In conclusion, the Taqman duplex real-time PCR method is a useful method for diagnosis and differentiation of WT-MS and MS1 vaccine strain in a single reaction.